THE REPRODUCTIVE BIOLOGY OF MUD CLAM (EAMESIELLA CORRUGATA) IN THE INTERTIDAL ZONE OF QUANG NINH PROVINCE - Thanh, Nguyen Xuan; Nhan, Dinh Van; Trang, Tran Thi Thu; Long, Luc Van; An, Tran Viet; Hung, Do Hong (Vietnam Journal of Marine Science and Technology, 2016)
360 samples of mud clam (Austriella corrugata) were collected in the intertidal zone of Quang Ninh province city from January 2015 to December 2015 for this study. The results showed that the gonad of female is black, that of male is milky white. The spawning season is from mid April to early September and the peak of spawning occurs from early June to early August. In spawning season, ratio of male/female is toward balance. In other months, rate of male is dominant in the population. Hermaphroditism occurs in the mud clam with a small percentage (from 3.3% to 10%) in the breeding season, in group with size of more than 40 mm. The length of mud clam at first sexual maturity is over 30 mm and the weight is over 20 g. The average absolute fecundity (Fa) is 960,680 eggs/individual. Development of mud clam larvae goes through main stages: Veliger, Umbo and Spat. Our findings contribute information to the planning of the artificial seed production, conservation and sustainable development of mud clam native resource.